The AI-Augmented Future: How Artificial Intelligence is Reshaping the Healthcare Workforce - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is no longer a futuristic concept; it is a rapidly evolving reality. From diagnostic imaging to...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics